Synthesis and anti-HCMV activity of 1-[ω-(phenoxy)alkyl]uracil derivatives and analogues thereof - Novikov, Mikhail S.; Babkov, Denis A.; Paramonova, Maria P.; Khandazhinskaya, Anastasia L.; Ozerov, Alexander A.; Chizhov, Alexander O.; Andrei, Graciela; Snoeck, Robert; Balzarini, Jan; Seley-Radtke, Katherine (Elsevier, 2013)
HCMV infection represents a life-threatening condition for immunocompromised patients and newborn infants and novel anti-HCMV agents are clearly needed. In this regard, a series of 1-[ω-(phenoxy)alkyl]uracil derivatives were synthesized and examined for antiviral properties. Compounds 17, 20, 24 and 28 were found to exhibit highly specific and promising inhibitory activity against HCMV replication in HEL cell cultures with EC₅₀ values within 5.5–12μM range. Further studies should be undertaken to elucidate the mechanism of action of these compounds and the structure–activity relationship for the linker region.
Keywords: Uracil derivatives; Nucleobase; HCMV; Antiviral; Nonnucleoside